Early globalization and the emergence of the elements of Islamic banking system - Balázs, Judit (Acta Scientiarum Socialium, 2013)
Early globalization and the emergence of the elements of Islamic banking system If we follow the forming processes of world economy it is unavoidable to find a link between the prevailing religion and economy. The question is how great the impact of the religion was on economy. Did the ruling religion play a role in the process during which certain societies and economies became the most developed in a century or even throughout centuries and did it contributed to their decline? Does religion have any role in the rise and fall of great powers? The present study is trying to find an answer to these questions in the case of Islam by analyzing the proliferation of the Islam, the belief of Islam, the premature Islamic capitalism, and early globalism. The early appearance of elements of Islamic banking system, the forerunner of the modern Western banking system, is analysed in details. In the 13th century, the Arab-Islamic world was an economic and military power. This age witnessed an early religious globalization, preceded by an economic globalization. Why was this model not able to maintain its leading position in the world? What was the role of Islam in that? Why did capitalism succeed in the Christian world, whereas its seeds had ap-peared in the Islamic world centuries before. The Islamic system that has evolved to the 12th–13th centuries essentially stopped developing up until the 20th century. While the ancient culture was reborn in Europe in the classical spirit of Athens and the Ro-man res publica, the societies of the Islamic world become stagnant. The presentation will be concluded and summarized by a critical analysis.